A critical review on bismuth and antimony halide based perovskites and their derivatives for photovoltaic applications: recent advances and challenges. Issue 32 (4th August 2020) - Jin, Zhixin; Zhang, Zheng; Xiu, Jingwei; Song, Haisheng; Gatti, Teresa; He, Zhubing
Abstract : The recent progress in photovoltaic applications of group VA metals (Bi and Sb) halide based perovskites and their derivatives are reviewed, addressing the limitations of and perspectives for these low toxicity lead-free photovoltaic materials. Abstract : In the past decade, lead halide perovskites experienced impressive progress in photovoltaics with the certified device conversion efficiency over 25%, owing to their outstanding optoelectronic properties. However, the toxicity and environmental instability of the core lead halide materials would strongly limit their commercialization. Within this scenario, research investigations directed at assessing the properties and opportunities offered by emerging lead-free halide perovskites are becoming everyday more relevant to pinpoint new low-cost/low-toxicity solutions for solar-to-electricity conversion. In this review, group VA metal halide based perovskites, namely those of bismuth (Bi) and antimony (Sb), and their derivatives with different valence states are classified based on the formulae A3 B2 X9 and A2 AgBX6, also known as double perovskites, and Ag a Bi b X a +3 b, called rudorffites (A = MA, FA, Cs, Rb, etc. ; B = Bi, Sb; X = I, Br, Cl). Here, we summarize the recent progress in the exploitation of these materials, with special attention devoted to the description of the crystal structures, thin film preparation methods and performances in real devices, including both theoretical insights and experimental observations. With this survey, we are able to provide reasonable perspectives for the future development of high-performance photovoltaic devices based on lead-free bismuth/antimony halide based perovskites and their derivatives.